Fables : the wolf among us. Volume 2 - Sturges, Lilah; Justus, Dave (DC Comics/Vertigo, 2016)
"As sheriff of Fabletown, Bigby Wolf has seen his share of unbelievable--and seemingly unsolvable--crimes. Before all that, though, he was faced with the greatest tests of his career ... Someone is killing people on Bigby's watch--now he and Snow White must intensify their search for an increasingly elusive and brutal killer. On the path to justice and retribution, they encounter secret passageways, mysterious new lands and some familiar faces from Fabletown. Fables: The Wolf Among Us is a gripping adaptation and expansion of the smash-hit video game from Telltale Games, and an official prequel to Bill Willingham's best-selling Fables! Written by Fables alum Matthew Sturges (Jack of Fables) and Dave Justus (House of Mystery), with art by Stephen Sadowski (JSA), Shawn McManus (Fables/Fairest), Eric Nguyen (Crossing Midnight) and Travis Moore (JSA All Stars)!"--